Conducting Global Adult Tobacco Survey (GATS) using Digital Technology in Bangladesh - Zaman, M Mostafa (Bangladesh Medical Journal, 2009)
<!--[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if !mso]> <![endif]--> <!--[if gte mso 10]> <![endif]--> DOI: 10.3329/bmj.v37i2.3587 Bangladesh Medical Journal 37(2) 2008 26-27